Foreign Policy Strategy of Indonesia and the United Kingdom in Indo-Pacific Regional Cooperation - Fathun, Laode Muhamad; Setiawan, Asep; Novialdi, Risky (Universitas Komputer Indonesia, 2025)
This article will discuss and explain the foreign policy formulation of Indonesia and the United Kingdom in the Indo-Pacific region. The urgency of this research emphasizes that both countries view maritime cooperation in the Indo-Pacific region as a crucial mechanism for national interests. However, the Indo-Pacific region is also a new front for conflict for major powers. Therefore, both countries must be able to employ a comprehensive strategy to become strategic partners. This research uses a qualitative methodology with a comparative model. Data collection techniques utilize literature and data analysis techniques using the tracing process. The results show that the two countries have different strategies in Indo-Pacific cooperation. This is based on differences in foreign policy orientation and identity. Furthermore, the different qualities and capacities of the two countries create differences in the formulation of their policy strategies. Indonesia applies the accommodation model, and the United Kingdom the alliance model. Keywords— Accommodation, Indo-Pacific, Indonesia, Leadership, Strategy, United Kingdom